REBALANCING HUMAN RIGHTS AT THE TIME OF COVID-19 PANDEMIC - Sandor, Judit (Pravni zapisi, 2020)
The year of 2020 will certainly be in all future books on the history of epidemiology and the Covid-19 pandemic will be discussed in them as perhaps the most significant public health challenge since the Spanish flu. But I also hope that it will feature as a new chapter in the books on health and human rights. The suffering of millions of people around the world, the deaths and medical challenges have already presented many lessons to learn from. One of the lessons should be to recognize the right to health as a full-fledged human and constitutional right that deserves a much closer attention whenever annual budgets are drafted and it should be considered as a fundamental human right without which no other rights can be exercised in epidemiological crises and even after that.